Prior Art Research in the Capstone Design Experience: A Case Study of Redesigned Online and In-person Instruction - Graham Sherriff; Dustin Rand (Issues in Science and Technology Librarianship)
Exploration of "prior art"—the state of a technology’s development, as manifested in literature, documentation, and artifacts—has many benefits for engineering students. It expands their understanding of the design problem, reveals a range of possible solutions, and develops research skills important to professional practice. While prior art often includes patents and research literature, it can include any type of publication or document. This paper presents an innovative approach to a prior art review assignment in the capstone course for mechanical, electrical, and biomedical engineering students at the University of Vermont (UVM). The assignment and accompanying instruction were redesigned in 2018–2019 to address several issues that limited students' ability to do the required work to a high standard. Foundational knowledge about key publication types and research skills was "flipped" into a set of online tutorials; the class session was converted from a lecture to an interactive workshop-style presentation; research consultations with an engineering librarian were tailored to team projects; and the assignment deliverables were redesigned to incorporate more reflection about the process of engaging with prior art. This multifaceted approach involves a substantial amount of preparation. However, assessment showed significant returns on the investment that includes improved knowledge of types of engineering publication, demonstrated use of advanced research practices, and insightful reflections on the role of prior art in design thinking.